2011
DOI: 10.5194/angeo-29-1037-2011
|View full text |Cite
|
Sign up to set email alerts
|

Average properties and small-scale variations of the mesospheric Na and Fe layers as observed simultaneously by two closely colocated lidars at 30° N

Abstract: Abstract. We report the average properties and small-scale variation features of the mesospheric Na and Fe layers at 30 • N from extensive simultaneous and common-volume Na and Fe lidar measurements at Wuhan, China. The annual mean Na and Fe density profiles are derived in terms of an averaging method taken from an early literature. The mean Na and Fe profiles preserve the sharp gradients present in most individual density profiles near the layer bottom. Near the bottommost of the layers the mean Na and Fe sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
4
22
1
Order By: Relevance
“…In other words, the Fe and Na density fluctuations are similar and in phase on the bottomsides and topsides of both layers and similar but 180°out of phase between the layer peaks. This behavior is similar to the observations reported by Chen and Yi [2011].…”
Section: Lidar Observationssupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, the Fe and Na density fluctuations are similar and in phase on the bottomsides and topsides of both layers and similar but 180°out of phase between the layer peaks. This behavior is similar to the observations reported by Chen and Yi [2011].…”
Section: Lidar Observationssupporting
confidence: 92%
“…[29] The larger gradient at the Fe and Na layer bottomside as compared to the topside has been characterized by Chen and Yi [2011] in great detail. This is also confirmed in our data.…”
Section: Density Gradient In the Boundary Correlationmentioning
confidence: 99%
“…It is found that both the top and bottom sides of the correlation profiles are positive, while the middle part is negative for all the three nights studied. This is the same as found by Chen and Yi [] over Wuhan, China, which indicates that this relationship may very well exist globally.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the values in the medium height range are negative and can reach −0.5 or less. The positive‐negative‐positive correlation as a function of altitude between Na and Fe is the same as that reported by Chen and Yi [] for lidar observations over Wuhan, China. The regions of negative values are 88.16–89.96, 90.56–93.56, and 90.54–96.24 km, respectively, for 2–3 July, 18–19, and 22–23 December 2003.…”
Section: Relationship Between Na and Fe Layersmentioning
confidence: 99%
“…Yi et al [] found that the lower boundaries of the simultaneously observed Fe and Na followed almost the same track. Chen and Yi [] showed for the first time that the Fe and Na fluctuations are positively correlated on both the bottomside and the topside of the layers, whereas they are typically negatively correlated near 90 km. These features have also been verified by the simultaneous Fe and Na observations at Arecibo Observatory (AO), Puerto Rico (18.35°N, 66.75°W) [ Yue et al ., ] and at Boulder, Colorado (40°N, 105°W) [ Huang et al ., ].…”
Section: Introductionmentioning
confidence: 99%